2012
DOI: 10.1038/jes.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of individual-based and group-based exposure estimation of microbial agents in health effects associated with a damp building

Abstract: We evaluated attenuation in linear associations between microbial exposure and respiratory symptoms occurring when individual measurements of microbial agents were used for estimating employees' exposure compared with group means. Symptoms, which improved when away from the building (building-related, BR), and measurements of culturable fungi, ergosterol, and endotoxin in floor dust were obtained between 2001 and 2007 from four cross-sectional studies on occupants of a water-damaged building. We compared odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Fungal exposure can be estimated through several means, including cultivation of viable spores and determination of chemical markers for fungi, typically cell wall components, such β ‐1,3 glucans and ergosterol. Ergosterol is a fungal membrane lipid that has been used as a chemical marker to determine fungal biomass from various environments, including indoors (Cho et al., ; Hyvärinen et al., ; Sordillo et al., ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal exposure can be estimated through several means, including cultivation of viable spores and determination of chemical markers for fungi, typically cell wall components, such β ‐1,3 glucans and ergosterol. Ergosterol is a fungal membrane lipid that has been used as a chemical marker to determine fungal biomass from various environments, including indoors (Cho et al., ; Hyvärinen et al., ; Sordillo et al., ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we cannot exclude the possibility that the lack of remediation effects on occupants’ health in our study might have resulted from persistent exposures in the building even after the various remediation activities. However, because we adjusted our statistical models for microbial exposures to endotoxin, ergosterol, and culturable fungi as time-varying covariates that were significant risk factors for various respiratory and non-respiratory symptoms in the same population [ 19 ], the potential confounding effects of these persistent exposures were likely to be minimized. A potential explanation of our findings might be that once respiratory or severe non-respiratory symptoms have developed in occupants of moisture-damaged buildings, physiological recovery in the affected employees might be compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Mean con- and microenvironment means between each pair of pollutants (see Table S2; results were similar for Spearman's correlation coefficients). 44 Rappaport and Kupper used a nested design with person nested within city (no person is in both cities) to examine 24-hour VOC exposures in the United States and found that typically half or more of the variance was within-person. The highest correlation observed was between PM 2.5 and BC at Eateries and weakest be- analysis.…”
Section: Re Sultsmentioning
confidence: 99%
“…Recent studies have examined the variance components for daily averaged PM 2.5, microbial agents, and volatile organic carbon. [44][45][46][47] In a study in Gothenburg, Sweden, 45 daily PM 2.5 concentrations measured among 29 subjects (<2 samples per participant, total n = 43) and variance was partitioned within and between participants and resulted in an ICC value equal to 0.62. ICC values tended to be less than 0.5 and approached zero for some elements, in PM 2.5 trace analysis.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation